2008
DOI: 10.1007/s15010-008-7334-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Signs as Dengue Markers During an Outbreak in Rio de Janeiro

Abstract: A combination of symptoms not necessarily considered indicative of dengue diagnosis could improve surveillance and medical decision-making in simple clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
2
9
0
2
Order By: Relevance
“…The pruritus usually coincides with the exanthema, but sometimes patients have only pruritus. Consistent with previous studies 25,26 , we observed a higher ratio of patients with pruritus compared to rash. It is known that pruritus is a common manifestation of cholestatic hepatitis 27 .…”
Section: Discussionsupporting
confidence: 93%
“…The pruritus usually coincides with the exanthema, but sometimes patients have only pruritus. Consistent with previous studies 25,26 , we observed a higher ratio of patients with pruritus compared to rash. It is known that pruritus is a common manifestation of cholestatic hepatitis 27 .…”
Section: Discussionsupporting
confidence: 93%
“…We did not find that fever, exanthema, thrombocytopenia (< 150,000), leukopenia (< 4,000) or vomiting were criteria to differentiate between patients who subsequently developed SDD versus N-SDD, as found in Brazil [39]. In another study, leukocyte count (< 4,500/μl) and thrombocyte count (< 90,000/μl), but not positive tourniquet test, were associated with spontaneous bleeding in patients from a DENV-endemic area [40].…”
Section: Discussionmentioning
confidence: 87%
“…Considering that the differential diagnosis of AFI and the notification of suspicious cases are based on combinations of those signs and symptoms, structured clinical history taken in sentinel units enables the acquisition of information useful for epidemiological surveillance. For instance, elevated agreement rates were found for the presence of exanthema (k = 0.941; 0.883-0.998) and history of itching (k = 0.755; 0.607-0.876), two clinical signs previously identified as useful for dengue diagnosis in the state of Rio de Janeiro [21]. It is worth noting that the possibility of collecting more detailed data, comprising information on intensity grading, is potentially innovative for clinical research in the field.…”
Section: Discussionmentioning
confidence: 99%